Tunisian engineers: protagonists of Tunisia’s modernisation. Two key moments: 1956 and 1987 - Amani Mansouri; Jorge Alonso Rodríguez Ortiz (Acta Polytechnica, 2024)
Engineers have played a key role in Tunisia’s modernisation process during and after its independence. They were crucial in almost all aspects of life. From the beginning of the reformist project, they were close to power and even made demands according to their interests. However, they did not know how to generate such cohesion within their group that would allow them to consolidate and have political influence. Two fundamental moments in the process of modernisation showing the evolution of a profession that went from the height of its splendour to its decline, with all that this meant and implied for all aspects of Tunisian life.